Peran Strategis Lobi dan Negosiasi dalam Berbagai Aspek - April Laksana; Aliya Dwi Rahayu; Hamdan Pahlepi; Ikmal Ikmal; Intan Inayah; Intan Nurul (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This study explores the essential role of lobbying and negotiation strategies across various sectors such as politics, social affairs, business, and non-profit organizations. Using a qualitative approach and case studies, the research highlights how these communication strategies influence decisions, build relationships, and resolve conflicts. The findings indicate that lobbying and negotiation skills are crucial for groups to achieve their goals, particularly in today’s digital era. Social media also emerges as a new platform for such practices, though it brings challenges to face-to-face interaction quality. Therefore, a deep understanding and ethical application of lobbying and negotiation are vital for creating effective and constructive communication.